PENGARUH BRAND IMAGE, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNAAN JASA (Studi Kasus (Penumpang KA Kaligung PT KAI DAOP IV Semarang) - Utomo, Prabowo Budi; Waloejo, Handoyo Djoko (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
The purpose of this study is to determine the effect of brand image, promotion and service quality to the usage seriveice decicion . This type of research is explanatory research. Sampling technique using sampling purposive. The number of samples taken as many as 100 respondents, which are the passanger of KA Kaligung. In this study assisted by IBM SPSS 16.0 system. The results showed that brand Image influence the usage service decicion by contributing 49,7% while the rest is influenced by factors other than bran Image. Promotion influences the usage service decicion by contributing 48,4% while the rest is influenced by factors other than promotion. Service quality influences the usage service decicion by contributing 51,8% while the rest is influenced by factors other than service quality. Meanwhile, simultaneously brand Image,promotion and service quality influence to the usage service decicion by donating 74% while the rest influenced by factors other than brand Image, promotion and service quality. Based on the calculation of Test F shows that there is a significant influence between brand image, promotion and service quality to the usage service decicion. This means the higher the brand image, promotion and service quality, the higher the usage service decicion of passanger of KA Kaligung. Suggestions in this research is to increase the brand image, promotion and service quality of KA Kaligung, so it can improve the the usage service decicion.